Use of mono- and sesquiterpenes for characterisation of mountain cheeses - Giuseppe ZEPPA; Manuela GIORDANO; Marta BERTOLINO; Vincenzo GERBI (Acta Agriculturae Slovenica)
Terpenes are volatile compounds originating exclusively from plants that can be found in dairy products. Several studies have therefore been conducted to use the terpenes to trace the geographical origin or the nature of the feed supplied to animals. The vegetation of mountain pastures varies which results in different types of foraging. Our aim was to determine if the terpene profile can be used to distinguish the mountain pasture of origin. The mono- and the sesquiterpenes of ricotta cheese samples produced during the summer in three mountain farms were then determined with SPME-GC-MS. The ricotta cheeses were produced with cow and goat milk and every three days of production a sample was analysed. Obtained results showed that these compounds vary widely between samples due to the stage of plant development but discrimination among the farms was still possible. Hence mono- and sesquiterpenes can be used not only to distinguish between summer pasture cheeses and the ones produced during other periods but also as markers of each mountain pasture.